1986 Guidelines for the treatment of mild hypertension: Memorandum from a WHO/ISH Meeting (1986)
The present guidelines were endorsed by the participants at the Fourth Mild Hypertension Conference, held at Königstein, Federal Republic of Germany, on 4-7 December 1985. They include the definition of mild hypertension, and describe blood pressure measurement, factors influencing the decision to begin treatment, methods of treatment, and follow-up. These guidelines are a revision of those produced in 1982; they are based on the best available scientific evidence, and will be updated in the future to keep abreast of further developments in this field.